Characterization of a Single-use Bioreactor for Pharmaceutical Applications for the Mixing of Non-newtonian Fluids - Federico Alberini; Martina Lo Chiano; Giuseppina Montante; Nicodemo Di Pasquale; Francesco Maluta; Alessandro Paglianti (Chemical Engineering Transactions, 2025)
In the pharmaceutical industry, single-use bioreactors (SUBs) are commonly employed due to their versatility and reduced risk of contamination between batches. Their applications range from vaccine production to the blending of formulated products. These formulations often exhibit non-Newtonian rheological behaviors which strongly affects mixing and whose behavior is not completed understood yet. For this study, we use a 50 L cubic tank, designed to mimic the geometry of a commercial SUB mixer. The shape and size of the vortex formed at the top of the vessel were monitored and measured using optical techniques. This study aims to investigate the effects of fluid level and agitation speed on energy consumption during mixing of shear-thinning fluids. Carboxymethylcellulose (CMC) solutions were examined in the SUB, and their rheological properties were characterized using a rheometer. The overall goal of this work is to enhance understanding of the mixing process for shear-thinning fluids by identifying optimal operating conditions based on agitation speed, filling level, and fluid rheology. Our results indicate that the rheology of the solution strongly affects the shape of the vortex and the trends of power per unit volume versus filling heights is affected drastically by the changes in rheology as well. These findings could contribute significantly to the development of more efficient and sustainable pharmaceutical processes.